2021
DOI: 10.3390/ijms22052781
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Compounds PRI-2191 and PRI-2205 Enhance Anastrozole Activity in Human Breast Cancer Models

Abstract: 1,25-Dihydroxycholecalciferol, the hormonally active vitamin D3 metabolite, is known to exhibit therapeutic effects against breast cancer, mainly by lowering the expression of estrogen receptors and aromatase activity. Previously, the safety of the vitamin D active metabolite (24R)-1,24-dihydroxycholecalciferol (PRI-2191) and 1,25(OH)2D3 analog PRI-2205 was tested, and the in vitro activity of these analogs against different cancer cell lines was studied. We determined the effect of the two vitamin D compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
(98 reference statements)
1
6
0
Order By: Relevance
“…Thus, combined use of calcitriol with one of three different AIs, namely exemestane, letrozole, or anastrozole, caused enhanced inhibition of MCF-7 cell growth [ 146 ]. Our studies confirmed these findings in human MCF-7 xenografted mice demonstrating tumor growth inhibition after treatment with new vitamin D analogs, PRI-2191 and PRI-2205, either alone or in combination with anastrozole [ 147 ]. In addition, Swami et al revealed that calcitriol acted as a selective aromatase modulator in mice, decreasing aromatase expression in the mammary adipose tissue and increasing it in bone marrow cells, but not altering the enzyme expression in the ovaries and uteri [ 148 ].…”
Section: Vitamin D and Breast Cancer Prevention And Treatmentsupporting
confidence: 78%
“…Thus, combined use of calcitriol with one of three different AIs, namely exemestane, letrozole, or anastrozole, caused enhanced inhibition of MCF-7 cell growth [ 146 ]. Our studies confirmed these findings in human MCF-7 xenografted mice demonstrating tumor growth inhibition after treatment with new vitamin D analogs, PRI-2191 and PRI-2205, either alone or in combination with anastrozole [ 147 ]. In addition, Swami et al revealed that calcitriol acted as a selective aromatase modulator in mice, decreasing aromatase expression in the mammary adipose tissue and increasing it in bone marrow cells, but not altering the enzyme expression in the ovaries and uteri [ 148 ].…”
Section: Vitamin D and Breast Cancer Prevention And Treatmentsupporting
confidence: 78%
“…More recently, it has been demonstrated that retinoids can block PR binding at shared DNA response element regions and inhibit P4 stimulated growth of ER-positive breast cancer xenografts, suggesting a cross-talk between PR and RAR in regulating a subset of hormone responsive breast cancer ( 188 ). It has also been shown that the addition of vitamin D analogs could potentiate the antitumor effect of the AI anastrozole in MCF7 tumor bearing mice via regulation of both VDR and ER signaling ( 189 ). In addition, VDR activation, with vitamin D or the synthetic analogue EB1089, could re-sensitize an antiestrogen resistant MCF7 breast cancer cell line to tamoxifen treatment and reduce the incidence of ER-positive mammary tumors in a preclinical model ( 190 ).…”
Section: Combination Strategiesmentioning
confidence: 99%
“…Another study has demonstrated that the VD active metabolite (24R)1,24-dihydroxycholecalciferol (PRI-2191) and the analog PRI-2205 significantly enhanced the antitumor activity of anastrozole in BC tumors and cells [ 155 ].…”
Section: Calcitriol In Combination With Endocrine Therapymentioning
confidence: 99%